It - Roach, Joseph R., 1947- (The University of Michigan Press, 2007)
That mysterious characteristic "It"--"the easily perceived but hard-to-define quality possessed by abnormally interesting people"--Roach traces the origins of "It" back to the period following the Restoration, persuasively linking the sex appeal of today's celebrity figures with the attraction of those who lived centuries before. The book includes guest appearances by King Charles II, Samuel Pepys, Flo Ziegfeld, Johnny Depp, Elinor Glyn, Clara Bow, the Second Duke of Buckingham, John Dryden, Michael Jackson, and Lady Diana, among others.--Publisher's description